The Influence of Digital Marketing and Electronic Word of Mouth on Purchase Decisions for Scarlett Whitening Products on Shopee - Fahyuda Rammadan; Agus Wibowo (LPPM Politeknik Pratama, 2026)
The development of e-commerce has driven companies to find the best way to perform digital marketing and use e-word of mouth in attempting to drive customers to buy a certain product. Cosmetic products are an engaging category, so most people make in-depth search efforts before buying, especially on the Shopee marketplace platform. This research will analyze how digital marketing and electronic word of mouth influence the purchase decision of Scarlett Whitening products through the Shopee platform. This research applies a quantitative approach with associative research. Data was collected from distributing questionnaires to 170 respondents who had purchased Scarlett Whitening products at Shopee. The data analysis techniques used included a validity test, reliability test, multiple linear regression analysis, t-test, and F-test using SPSS software. The study findings indicate that digital marketing has a positive and significant effect on purchase decisions. In addition, it was also able to prove that electronic word of mouth has a positive effect on purchase decisions. Simultaneously, digital marketing and e-WOM substantially affect the Purchase decision of Scarlett Whitening products at Shopee, with digital marketing being the most dominant variable. These findings suggest that the quality of digital content, the clarity of product information, and the reliability of consumer reviews are important factors affecting consumer purchase decisions